Kualitas Prosedur Audit Siklus Aset Tetap dan Implikasinya terhadap Deteksi Salah Saji Material - Sukmawati, Sukmawati; Nur Fadila Salju; Masyhuri, Masyhuri (Journal of Economics, Management, and Accounting, 2025)
This study discusses the importance of audit procedure quality in the fixed asset cycle as a determining factor in the auditor's success in detecting material misstatements in financial statements, given that fixed assets are accounts that are prone to estimation errors, recording inaccuracies, and internal control weaknesses. The research method used is descriptive qualitative with a literature study approach, where data is obtained through searching national and international journals published in the last ten years that are relevant to fixed asset audits, material misstatements, and the effectiveness of audit procedures, then analyzed using content analysis techniques to identify patterns and key findings. The results of the study show that the quality of audit procedures, especially those covering physical verification, document reconciliation, accounting estimate evaluation, and substantive testing, has a significant effect on the auditor's ability to detect material misstatements, especially in environments with high governance risks. The discussion shows that auditor competence, internal control effectiveness, and external governance conditions determine audit effectiveness. This study concludes that the implementation of robust, risk-based audit procedures improves the reliability of financial statements and strengthens stakeholder confidence.